2019
DOI: 10.1155/2019/5176705
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection in the IOT Health Environment Using Modified Recursive Feature Selection

Abstract: The accurate and efficient diagnosis of breast cancer is extremely necessary for recovery and treatment in early stages in IoT healthcare environment. Internet of Things has witnessed the transition in life for the last few years which provides a way to analyze both the real-time data and past data by the emerging role of artificial intelligence and data mining techniques. The current state-of-the-art method does not effectively diagnose the breast cancer in the early stages, and most of the ladies suffered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…McKinney et al [ 38 ] proposed an AI system that outperformed human experts in breast cancer prediction on mammogram images. Memon et al [ 39 ] suggested using a modified recursive feature selection algorithm that achieved 99% accuracy with an SVM classifier on the WDBC dataset. Ronoud and Asadi [ 40 ] suggested using the genetic algorithm (GA) to evolve the number of hidden layers and neurons and to finetune the network weights and biases of the deep belief network (DBN).…”
Section: Related Workmentioning
confidence: 99%
“…McKinney et al [ 38 ] proposed an AI system that outperformed human experts in breast cancer prediction on mammogram images. Memon et al [ 39 ] suggested using a modified recursive feature selection algorithm that achieved 99% accuracy with an SVM classifier on the WDBC dataset. Ronoud and Asadi [ 40 ] suggested using the genetic algorithm (GA) to evolve the number of hidden layers and neurons and to finetune the network weights and biases of the deep belief network (DBN).…”
Section: Related Workmentioning
confidence: 99%
“…The performance evaluation metrics [25], [39], [40] are use for performance evaluation of the model such as accuracy, specificity, sensitivity, F1-score, MCC, ROC and AUC. These metrics are described mathematically in equation 5-10 respectively.…”
Section: E Performance Evaluation Metricsmentioning
confidence: 99%
“…Sangaiah and Kumar [16] have suggested an algorithm which is a hybrid-type detection system for the breast cancer diagnosis. For the early detection of breast cancer, the suggested algorithm utilized a ReliefF quality reduction with entropy based genetic algorithm.…”
Section: A Breast Cancermentioning
confidence: 99%